(untitled) (International Congress on Economics, Management and Business Studies, 2026)
In mechanical processing workshops, the efficiency of the labor process and the health of workers largely depend on factors of the industrial environment, including the level of lighting. Based on statistical and experimental data presented by the World Health Organization (WHO), the International Labour Organization (ILO), and leading scientific sources in industrial hygiene, it has been scientifically substantiated that insufficient lighting increases the risk of visual fatigue, occupational injuries, and production errors. Lighting is one of the oldest yet still highly relevant factors of industrial hygiene.